2014
DOI: 10.1186/1757-7241-22-24
|View full text |Cite
|
Sign up to set email alerts
|

Basic life support knowledge, self-reported skills and fears in Danish high school students and effect of a single 45-min training session run by junior doctors; a prospective cohort study

Abstract: BackgroundEarly recognition and immediate bystander cardiopulmonary resuscitation are critical determinants of survival after out-of-hospital cardiac arrest (OHCA). Our aim was to evaluate current knowledge on basic life support (BLS) in Danish high school students and benefits of a single training session run by junior doctors.MethodsSix-hundred-fifty-one students were included. They underwent one 45-minute BLS training session including theoretical aspects and hands-on training with mannequins. The students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 19 publications
4
53
2
5
Order By: Relevance
“…Similar results were found by other authors (8) in a study with Danish students (average age of 17.5±1.2 years) and students from 13 European countries (26) . Some studies have shown that even individuals who had training presented low values of knowledge (25,27) and some said they did not feel prepared (16,26) . Still, it is proven that adult training in BLS is effective and necessary (28)(29) , reinforcing the need for recycling and updating knowledge (7) .…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were found by other authors (8) in a study with Danish students (average age of 17.5±1.2 years) and students from 13 European countries (26) . Some studies have shown that even individuals who had training presented low values of knowledge (25,27) and some said they did not feel prepared (16,26) . Still, it is proven that adult training in BLS is effective and necessary (28)(29) , reinforcing the need for recycling and updating knowledge (7) .…”
Section: Discussionsupporting
confidence: 91%
“…Critically ill patients and casualties are referred to tertiary teaching hospitals. The evidence shows that bystander CPR can double or triple survival rates after cardiac arrest (16)(17)(18). However, according to the guidelines, CPR teams in hospitals should be called when necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Successful resuscitation following out-of-hospital cardiac arrest (OHCA) depends on the links in the chain of survival; early recognition and immediate bystander cardiopulmonary resuscitation increase the survival rate twofold to threefold [1,2]. Ventricular fibrillation is the most frequent rhythm in OHCA, and for every minute that defibrillation is delayed, the chance of survival is reduced by 10-12 % [3, 4].…”
mentioning
confidence: 99%
“…Less than one-third of witnessed OHCA victims receive bystander CPR [2]. Educational efforts can increase the application of bystander CPR and increase the use of AEDs [1,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation